Varieties of Democracy (V-Dem) - Teorell, Jan; Lindberg, Staffan I.; Gerring, John; Coppedge, Michael; Skaaning, Svend-Erik (University of Gothenburg, 2014)
Varieties of Democracy (V-Dem) is a new approach to conceptualizing and measuring democracy. It is a collaboration among more than 50 scholars worldwide which is co-hosted by the Department of Political Science at the University of Gothenburg, Sweden; and the Kellogg Institute at the University of Notre Dame, USA.

With four Principal Investigators, two Program managers, fifteen Project Managers, more than thirty Regional Managers, almost 200 Country Coordinators, and approximately 2,800 Country Experts, the V-Dem project is one of the largest social science data collection projects focusing on research.

V-Dem collects data for 350+ indicators across a wide range of democracy aspects. Electoral democracy is in the centre and linked to this concept we find six additional dimensions of democracy: liberal, majoritarian, deliberative, participatory, consensual and egalitarian. In addition to a number of main indices, data is broken down into a number of components that are available to the user along with all indicators. Through the unique character of the database, old and new questions about the nature, growth and survival of democracy can be tested in a way not possible before.

Data is available for 177 countries from 1900 to 2016. Altogether, the database consists of approximately 17 million data points. The database is updated annually and new datasets are launched every year in the spring.

The dataset is available for download here: https://www.v-dem.net/en/data/data-version-7-1/

The data can also be explored online via: https://www.v-dem.net/en/analysis/

Purpose:

The world's largest database on democracy. The database provides 350+ indicators for 177 countries 1900-2016.

Varianter på Demokrati (V-Dem) är en ny approach till konceptualisering och mätning av demokrati. Projektet drivs av V-Dem Institutet vid Statsvetenskapliga institutionen, Göteborgs Universitet tillsammans med Kellogg Institutet vid Notre Dame University i USA.

V-Dems nätverk sträcker sig över hela världen och involverar ett stort antal forskare. Med fyra Principal Investigators, två projektledare, femton nyckelforskare, mer än 30
Regional Managers, 200 Country Coordinators, samt 2800 Country Experts så är V-Dem ett av de största samhällsvetenskapliga forskningsprojekten någonsin.

V-Dem samlar in data för 350+ indikatorer över ett brett spektra av aspekter av demokrati. I centrum finns electoral demokrati, och knutet till detta koncept finner vi sex ytterligare dimensioner av demokrati: liberal, majoritarian, deliberative, participatory, consensual och egalitarian. Utöver ett antal huvudindex så bryts data ner i ett antal komponenter som finns tillgängliga för användaren tillsammans med samtliga indikatorer. Genom databasens unika karaktär kommer gamla och nya frågeställningar om demokratins natur, framväxt och överlevnad att kunna prövas på ett sätt som aldrig tidigare varit möjligt.

Data finns tillgänglig för 177 länder från 1900-2016. Sammantaget så består databasen av ca 17 miljoner datapunkter. Databasen uppdateras årligen och nya dataset lanseras varje år under våren.

Data kan laddas ner här: https://www.v-dem.net/en/data/data-version-7-1/

Datan kan även visualiseras online här: https://www.v-dem.net/en/analysis/

Syfte:

Världens största databas på demokrati. Databasen tillhandahåller 350+ indikatorer for 173 länder för 117 år.
Varieties of Democracy (V-Dem)
Keywords: politics; politik; political institutions; politiska institutioner; democracy; demokrati; political change; politisk förändring; democratization; demokratisering; political systems; politiska system; political indicators; politiska indikatorer; representative democracy; representativ demokrati; parliamentary systems; parlamentariska system; political issues; politiska frågor; political, social and economic issues; politiska, sociala och ekonomiska frågor; POLITICS; POLITIK; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Conflict, security and peace; Konflikter, säkerhet och fred; Social conditions and indicators; Sociala förhållanden och indikatorer; Political Science; Statsvetenskap